The Cat in the Hat comes back! - Seuss, Dr.; Random House (Firm); Beginner Books (New York : Beginner Books, 1958)
The Cat in the Hat leaves a big pink ring in the tub and moves it from place to place with the help of his alphabet friends
450
AR
Accelerated Reader AR
Accelerated Reader/Renaissance Learning
Reading Counts RC
Accelerated Reader
Keywords: Cats -- Juvenile poetry; Snow removal -- Juvenile poetry; Cleaning -- Juvenile poetry; Wit and humor, Juvenile; Fantasy; Stories in rhyme; Stories in rhyme